The Plant V-ATPase - Seidel, Thorsten (Frontiers in Plant Science, 2022)
V-ATPase is the dominant proton pump in plant cells. It contributes to cytosolic pH homeostasis and energizes transport processes across endomembranes of the secretory pathway. Its localization in the trans Golgi network/early endosomes is essential for vesicle transport, for instance for the delivery of cell wall components. Furthermore, it is crucial for response to abiotic and biotic stresses. The V-ATPase’s rather complex structure and multiple subunit isoforms enable high structural flexibility with respect to requirements for different organs, developmental stages, and organelles. This complexity further demands a sophisticated assembly machinery and transport routes in cells, a process that is still not fully understood. Regulation of V-ATPase is a target of phosphorylation and redox-modifications but also involves interactions with regulatory proteins like 14-3-3 proteins and the lipid environment. Regulation by reversible assembly, as reported for yeast and the mammalian enzyme, has not be proven in plants but seems to be absent in autotrophic cells. Addressing the regulation of V-ATPase is a promising approach to adjust its activity for improved stress resistance or higher crop yield.